NORWEGIAN’S RESPONSE TOWARD NAZI’S IDEOLOGY IN JOHN STEINBECK’S THE MOON IS DOWN - IQBAL TAWAKAL KURNIANTO (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2013)
In a novel, it is often found that there is a character which becomes a center of the problem in a novel. But sometimes, there is also a novel that does not use a character to be the center of the story in that novel or the author uses a group or an organization that is the beginning of the problem in the story. This research is used to reveal how the role of a group or an organization in case of building a completed story is. A group or an organization which will be analyzed here is a group or an organization in The Moon Is Down written by John Steinbeck that is Nazi. To analyze Nazi in that novel, a theory which are brought by Stephen Greenblatt is used, New Historicism. This theory is chosen because the related to the creation of a story and the reality that had happened. By using New Historicism, it will be easy to understand the position of Nazi which is created by the processes in the story and the reality that had happened. A result of this research will be an explanation about how the Nazi in the story is made and how Nazi affects a story so there is an understanding about the story that include a value and an understanding of Nazi itself. Keywords: Nazi, response, ideology